2020
DOI: 10.1136/bmjdrc-2019-001026
|View full text |Cite
|
Sign up to set email alerts
|

Association of the IgGN-glycome with the course of kidney function in type 2 diabetes

Abstract: IntroductionInflammatory processes are thought to be involved in kidney function decline in individuals with type 2 diabetes. Glycosylation of immunoglobulin G (IgG) is an important post-translation process affecting the inflammatory potential of IgG. We investigated the prospective relationship between IgG N-glycosylation patterns and kidney function in type 2 diabetes.Research design and methodsIn the DiaGene study, an all-lines-of-care case–control study (n=1886) with mean prospective follow-up of 7.0 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 47 publications
(32 reference statements)
3
18
0
Order By: Relevance
“…In an effort to better predict and formulate treatment to prevent and/or delay diabetic kidney function deterioration, recent studies have identified a strong association between type 2 diabetes and N-linked glycosylation of proteins [74,75]. In particular, the presence of glycosylated immunoglobulin G (IgG), glycosylation of which affects the inflammatory potential of IgG, was prospectively evaluated in the DiaGene study over a mean follow-up of 7 years in a large cohort of diabetic patients [75]. Thereafter, the association was evaluated between 58 IgG N-glycan profiles and the estimated glomerular filtration rate (eGFR) as well as albumin-to-creatinine ratio (ACR).…”
Section: Peritoneal Ultrafiltration Failurementioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to better predict and formulate treatment to prevent and/or delay diabetic kidney function deterioration, recent studies have identified a strong association between type 2 diabetes and N-linked glycosylation of proteins [74,75]. In particular, the presence of glycosylated immunoglobulin G (IgG), glycosylation of which affects the inflammatory potential of IgG, was prospectively evaluated in the DiaGene study over a mean follow-up of 7 years in a large cohort of diabetic patients [75]. Thereafter, the association was evaluated between 58 IgG N-glycan profiles and the estimated glomerular filtration rate (eGFR) as well as albumin-to-creatinine ratio (ACR).…”
Section: Peritoneal Ultrafiltration Failurementioning
confidence: 99%
“…[73] Glycosylation profile Type 2 diabetes Different IgG N-glycosylation patterns in diabetes. [75] MALDI-TOF-MS and glycosylation profile Different PD solutions over time Increase of an IgG glycosylation pattern over time and in peritonitis. [67] 2DE and SELDI-TOF-MS Peritonitis Increased in peritonitis: B2M.…”
Section: Proteomic Strategy Condition Findings Referencementioning
confidence: 99%
“…An increase in antennary fucosylation of α 1 -acid glycoprotein was related with vascular complications in patients with type 1 diabetes [ 23 ]. In patients with type 2 diabetes, a faster decline of kidney functions was associated with IgG glycans containing more bisecting GlcNAc and increased fucosylation with bisecting GlcNAc, whereas fucosylation without bisecting GlcNAc was associated with a slower kidney deterioration [ 24 ]. Inhibition of core-fucosylation alleviated kidney damage and fibrosis in a diabetic mouse model [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Bisecting N-acetylglucosamine (GlcNAc) and complex N-glycan structures exert a pro-inflammatory effect, while the addition of galactose, sialic acid, or fucose has an antiinflammatory effect. 9 Recently, variations in IgG glycans have emerged as potential biomarkers and therapeutic targets of various metabolic diseases, such as aging, 10 dyslipidemia, 11 immune disease, 12 type 2 diabetes, 13,14 and diabetic nephropathy. 9 In fact, type 2 diabetes is accompanied by glucose metabolic disorder and imbalanced regulation of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recently, variations in IgG glycans have emerged as potential biomarkers and therapeutic targets of various metabolic diseases, such as aging, 10 dyslipidemia, 11 immune disease, 12 type 2 diabetes, 13,14 and diabetic nephropathy. 9 In fact, type 2 diabetes is accompanied by glucose metabolic disorder and imbalanced regulation of inflammation. Moreover, IgG glycosylation profiles interact with risk factors for type 2 diabetes, such as obesity, 15 blood pressure, 16,17 and FBG.…”
Section: Introductionmentioning
confidence: 99%